LAW ENFORCEMENT AGAINST THE MISUSE OF SOCIAL ASSISTANCE FUNDS FOR MSMES IN CIREBON REGENCY IN 2020 (CASE STUDY OF WARUKAWUNG AND WANGUNHARJA VILLAGES) - Fauzi, Agam; Junaedi; Mawar Kartina, Ratu (Hukum Responsif, 2024)
The right to receive social assistance is an important right and can help the basic needs of the community. The significance of the importance that every citizen has the right to decent work and livelihood. Social assistance is assistance provided to people who experience social risks. The assistance provided can be in the form of goods or cash. Social assistance is assistance in the form of goods, money or services to individuals, families, groups or communities that are less fortunate. With Law number 14 of 2019 is an amendment to Law number 11 of 2009 concerning social welfare. The formulation of the problem raised by the author is about how the law enforcement process related to the misuse of social assistance funds and how to be responsible for the misuse of social assistance funds The author's research method uses normative juridical methods, types of qualitative research, and research specifications using descriptive analysis. The data used are primary and secondary data obtained through laws and regulations and interviews with agencies related to this research, namely the Cirebon Police and the Cirebon Regency Social Service. The conclusion of the author's research is to find out the law enforcement process related to the misuse of social assistance funds along with accountability efforts for the misuse of social assistance funds